Trauma craniano violento pediátrico : estratégias de avaliação e prevenção - Lopes, Nahara Rodrigues Laterza (Universidade Federal de São Carlos, 2017)
The present dissertation is composed of a compendium of four scientific papers with the common theme of prevention of abusive head trauma (AHT), a serious type of infant maltreatment. The first article describes a review of the Brazilian and international literature on the main strategies of AHT prevention. A total of 34 articles describing 20 initiatives to prevent AHT were selected, five of which aimed at reducing infant crying, three aimed at caregiver’s emotional regulation, and 12 aimed at raising parents and caregivers’ awareness on AHT. Among them, parental education about infant crying and risks of shaking a baby stands out for its empirical evidence. The second article describes the process of elaboration and assessment of validity evidence based on internal structure of the Attitudes towards an Infant Crying Scale, developed for evaluation of parental attitude towards the baby's crying during the first months of life. After exploratory factor analysis, the final version of the scale was composed of 50 items, divided into six components: Consequences of Shaking the Baby, Welfare of the Caregiver, Strategies Targeting the Baby, Strategies Targeting the Caregiver, Beliefs about Baby Care and Characteristics of Infant Crying. The scale appears to be promising with respect to the objective of evaluating the attitude of parents and caregivers about infant crying and in evaluating AHT prevention programs. The third study describes the evaluation of a brief intervention to increase knowledge on AHT among parents of children up to two years old. A total of 254 parents who attended pregnancy or puerperal groups in six municipalities in the State of São Paulo participated in the study. Participants were randomly assigned to one of two conditions: Experimental Group (EG) or a waiting list Control Group (CG). The intervention involved showing an educational video and reading a pamphlet on AHT. To measure parental knowledge, the Attitudes towards the Infant Crying Scale was used. An increase in participants' knowledge about consequences of shaking, caregiver’s wellbeing, caregiver strategies to deal with crying, beliefs about infant care and about characteristics of infant crying were observed in the EG at posttest. Finally, the fourth article describes the evaluation of a training program for Health Care professionals about AHT. The training consisted of a four-unit course (two hours per unit), in which the topics of family violence, child abuse, abusive head trauma and prevention strategies were addressed. A total of 13 professionals from Basic Health Units from a city in the State of São Paulo participated in the study. Participants were randomly divided into two groups: Experimental Group (EG) and a Wait-List Control Group (CG). The experimental design for the EG was pre-test - intervention - post-test - follow-up and for the CG was pre-test 1 - pre-test 2 - post-test - intervention. The Attitudes towards the Infant Crying Scale was used. After training, participants' knowledge about caregiver strategies to deal with crying related to caregiver and to baby and characteristics of infant crying increased for EG participants. The increase in knowledge about caregiver strategies to deal with crying related to caregiver and characteristics of infant crying was maintained at follow-up, suggesting the effectiveness of this training in increasing knowledge on AHT among health professionals.
Keywords: Síndrome do bebê sacudido; Prevenção; Maus-tratos físicos; Shaken baby syndrome; Prevention; Physical abuse; CIENCIAS HUMANAS::PSICOLOGIA